Application of nanotechnology for enhancing oil recovery – A review - Chegenizadeh, N.; Saeedi, Ali; Xie, Q. (2016)
Nanotechnology has attracted a great attention in enhancing oil recovery (EOR) due to the cost-effective and environmental friendly manner. The size of nanoparticles for EOR usually is in a range of 1e100 nm, which may slightly differ from various international organisations. Nanoparticles exhibit significantly different properties compared to the same fine or bulk molecules because of much higher concentration of atoms at their surface as a result of ultra-small size. In particular, one of the most useful and fascinating properties of these particles is to creating a massive diffusion driving force due to the large surface area, especially at high temperatures. Previous studies have shown that nanoparticles can enhance oil recovery by shifting reservoir wettability towards more water-wet and reducing interfacial tension, yet this area is still open for discussion. It is worth noting that the potential of nanoparticles to reduce the oil viscosity, increase the mobility ratio, and to alter the reservoir permeability has not been investigated to date. Depending on the operational conditions of the EOR process, some nanoparticles perform more effectively than others, thus leading to different levels of enhanced recovery. In this study, we aim to provide a summary on each of the popular and available nanoparticles in the market and list their optimum operational conditions. We classified nanoparticles into the three categories of metal oxide, organic and inorganic particles in this article.